AP-PACVD plasma printer: investigating the influence of gas flow rates to printing resolution in parallel with CFD simulation. (7th September 2021) - Acharya, Kishor; Bulou, Simon; Gaulain, Thomas; Choquet, Patrick
Abstract: A coaxial shaped atmospheric pressure plasma torch has been used to deposit the millimetric scale plasma polymer. A detailed experiment has revealed the appearance of three different kinetic regimes with distinct coating morphology: no deposition, circular dot and circular ring formation. The ratio of precursor carrier gas flow to the plasma species carrier gas flow has been identified as crucial factor to separate the three regimes. Further experiments regarding the influence of precursor mass fraction on the dimension and deposition rates has been performed for a circular dot regime to get more insights into the coating shape, size and volume and its relation to gas flow dynamics. A side by side computational fluid dynamic simulation coupled with species transport module has been performed to understand the influence of flow dynamics on coating morphology. The appearance of recirculatory vortices in-between the nozzle and substrate and its role on confinement of precursor at specific region and mixing of plasma species to precursor has been highlighted. A good correlation in between the diameter of thus coated plasma polymer in circular dot regime and the simulated confinement zone is here reported.